2012
DOI: 10.1111/j.1549-0831.2011.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

From Game Protection to Wildlife Management: Frame Shifts, Organizational Development, and Field Practices

Abstract: One enduring question in social movements research is the relationship between cultural representations and organizational structure. In this article, we examine the development of different discursive frames over time, and how such frame shifts affect movement structure and practices. This approach seeks to illuminate the dialectical interplay between the movement community's discursive frame and its practices, and thus expand our understanding of the process of social movement growth and change. Through a cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In this tradition, research on the American environmental movement specifically has found that organizations are actually penalized for adopting a strategy of diversification (Olzak & Johnson, 2019). However, research shows that it is more often the case that movements and organizations experience a payoff as a result of issue diversification (Aldrich, 1979; Carroll, 1985; Edwards & Marullo, 1995; Heaney & Rojas, 2014; Walker & McCarthy, 2010) and this is particularly true for their ability to accumulate resources (Brulle & Benford, 2012; Cornfield & Fletcher., 1998; Johnston, 1980). Our research challenges this trend by showing that issue diversity does not have a significant impact on mobilization outcomes as measured by income, FTE staff, and members.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this tradition, research on the American environmental movement specifically has found that organizations are actually penalized for adopting a strategy of diversification (Olzak & Johnson, 2019). However, research shows that it is more often the case that movements and organizations experience a payoff as a result of issue diversification (Aldrich, 1979; Carroll, 1985; Edwards & Marullo, 1995; Heaney & Rojas, 2014; Walker & McCarthy, 2010) and this is particularly true for their ability to accumulate resources (Brulle & Benford, 2012; Cornfield & Fletcher., 1998; Johnston, 1980). Our research challenges this trend by showing that issue diversity does not have a significant impact on mobilization outcomes as measured by income, FTE staff, and members.…”
Section: Discussionmentioning
confidence: 99%
“…Although research on specialization has focused on the implications of diversification or specialization on the life span of a population of organizations, a separate body of work has focused on how issue framing, and frame extension in particular, is related to various mobilization outcomes such as the accumulation of valuable human resources (Benford & Snow, 2000; Brulle & Benford, 2012; Cornfield & Fletcher., 1998; Edwards & McCarthy, 2004; Johnston, 1980; Snow et al, 1986). Frame extension is related to issue foci because it highlights how groups can focus on a narrower set of issues or connect a larger set of issues through meaning making work.…”
Section: Strategy and Issue Focusmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the prominence of major international NGOs impacting corporate environmental action, we select the following five cases-Conservation International, Friends of the Earth, Global Witness, Greenpeace andWWF-between 2002 and2017. We adopt the well-established view that actors motivate action by giving sense to their stakeholders through various sentiments, also referred to as emotional framing (Pesqueira et al, 2020;Raffaelli, Glynn, & Tushman, 2019;Reber & Berger, 2005;Reinecke & Ansari, 2016). It is common to study framing shifts in organisational communication of NGOs, including their social media accounts (Ji, Harlow, Cui, & Wang, 2018), news media coverage (Brulle & Benford, 2012) and press releases (Luxon, 2019). We also study 5880 press releases issued by these NGOs and investigate framing shifts concerning 225 of the largest multinational companies (MNCs).…”
Section: Introductionmentioning
confidence: 99%